2016
DOI: 10.3389/fmicb.2016.01681
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Production in Response to Staphylococcal MS-1 Phage Cocktail in Patients Undergoing Phage Therapy

Abstract: In this study, we investigated the humoral immune response (through the release of IgG, IgA, and IgM antiphage antibodies) to a staphylococcal phage cocktail in patients undergoing experimental phage therapy at the Phage Therapy Unit, Medical Center of the Ludwik Hirszfeld Institute of Immunology and Experimental Therapy in Wrocław, Poland. We also evaluated whether occurring antiphage antibodies had neutralizing properties toward applied phages (K rate). Among 20 examined patients receiving the MS-1 phage coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 28 publications
1
82
0
1
Order By: Relevance
“…Interestingly, the level of antibody responses was not correlated with the outcome of therapy. What is more, high antibody levels were detected in 43% of patients treated with phage cocktails versus only in 17% of patients on monotherapy [23,24]. The S. aureus phage cocktails were composed of three phages: S. aureus A5/80, S. aureus P4/6409 and S. aureus 676/Z.…”
Section: • Phage Interactions With Lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the level of antibody responses was not correlated with the outcome of therapy. What is more, high antibody levels were detected in 43% of patients treated with phage cocktails versus only in 17% of patients on monotherapy [23,24]. The S. aureus phage cocktails were composed of three phages: S. aureus A5/80, S. aureus P4/6409 and S. aureus 676/Z.…”
Section: • Phage Interactions With Lymphocytesmentioning
confidence: 99%
“…Phages vary in their immunogenicity, and the humoral response also depends on the route of administration, dose and the patient's immune status [23,24]. Recently, we presented a vision to develop and establish a bank of phages specific to the most threatening pathogens and armed with homing peptides enabling their selective localization in infected tissues and stable eradication of infection [25].…”
Section: • Phage Interactions With Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phage engineering can be employed to keep bacterial killing property but bypass lysis induced endotoxin release and related side effect [127]. More recently, human humoral immune response against phage therapy showed that anti-phage antibodies (Abs), including IgM, IgG and IgA, were detected in patient sera when staphylococcal MS-1 phage cocktail was used for treatment [128]. Interestingly, these anti-phage Abs did not compromise the final efficacy [128].…”
Section: Discussionmentioning
confidence: 99%
“…[19,[29][30][31][32], l'administration de phages peut, dans certains cas, s'accompagner de la production d'anticorps dont certains sont neutralisants (provoquant l'inactivation de la particule virale) [33,34]. Les conséquences cliniques liées à la présence de ces anticorps ne semblent cependant pas influencer le pronostic infectieux et l'efficacité du traitement [35].…”
Section: Prêt-à-porter Et Sur Mesureunclassified